Laparoscopic-Assisted Transumbilical Extracorporeal Resection of Meckel’s Diverticulum in 10 years old boy with symptoms of gastrointestinal bleeding - K, Karavdić; A, Firdus; A, Mešić; S, Rahmanović; R, Milardović; A, Đuran (Archives of Surgery and Clinical Research, 2020)
The Meckel’s diverticulum (MD) is the most common anomaly of ductus omphaloentericus that surgeon encounters in clinical practice. The accurate incidence is unknown because most patients with the Meckel’s diverticulum are asymptomatic. Most studies report an incidence of about 2%. Approximately 4% of patients with the Meckel’s diverticulum become symptomatic. A 10 years old boy, was sent from regional hospital. His symptoms started the day before he was hospitalized and represented as gastrointestinal bleeding, lower abdominal pain and four times vomiting, without fever. Ultrasound and X-ray of the abdomen were normal. Blood findings showed: RBC 3,19, hemoglobin 0,95, hematocrit 0,27. During a physical examination abdomen was palpatory soft, with no presence of the pain. Digital rectal examination showed blood. A scintigraphy pathologic scan showed a focal lesion of the right hemi abdomen consistent with the Meckel’s diverticulum.Patient was treated byLaparoscopic-Assisted Transumbilical Extracorporeal Resection of the Meckel’s Diverticulum.